Strategies to Improve Work Performance - Pardomuan H. Siregar, Raja; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to complete the final assignment requirements for obtaining a master's degree, and another aim of this research is to provide input for organizations so that they can develop better. Every person is unique in their needs, desires, interests, values, beliefs, attitudes, mental processes. , perception, and personality, among others (Umam, 2012). An organization or corporation is founded on the basis of a vision for the benefit of human interests, and humans are the ones who regulate the implementation of the mission of the organization or company. Human interaction begins with communication. Humans can interact with each other through communication in various environments, including markets, workplaces, homes, and public spaces. No one in this world would avoid participating in his talks. The results of this research are as follows: Work Ethics has a positive and significant effect on Competency with an original sample value of 0.652 p value 0.000. Work Ethics has a positive and significant effect on Work Performance with an original sample value of 0.429 and ap value of 0.002. Competency has a positive and significant effect on Job Performance with an original sample value of 0.419 and ap value of 0.000. Communication has a positive and significant effect on competence with an original sample value of 0.243 and ap value of 0.014. Communication has a positive and insignificant effect on Job Performance with an original sample value of 0.090 and ap value of 0.228. Work Ethics has a positive and significant effect on Work Performance through Competency indirectly with an original sample value of 0.273 and ap value of 0.001. Communication has a positive and significant effect on Job Performance through Competency with an original sample value of 0.102 and ap value of 0.044.